Effectiveness of gutta-percha and Resilon in filling lateral root canals using the Obtura II System - Tanomaru-Filho, Mario [UNESP]; Sant'anna-Junior, Arnaldo [UNESP]; Bosso, Roberta [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP] (Sociedade Brasileira de Pesquisa Odontológica (SBPqO), 2011)
The aim of this study was to evaluate the effectiveness of gutta-percha and Resilon in filling lateral root canals by using the Obtura II system. Root canals of artificial teeth were prepared using a standard protocol, and lateral canals were made in three thirds of the root canal. The root canals were filled with either Obtura gutta-percha (OB), Endopoints flow gutta-percha (ED), or Resilon (RE) by using the Obtura II system. The fillings were evaluated using digitized radiographs and analyzed by using Image Tool software. Outlines of the total areas of the lateral canals and the filled areas were used to determine the percentage of filling in each lateral canal. Data were analyzed with the Kruskal Wallis and Dunn tests at a 5% significance level. RE and ED showed better results than OB did in the three thirds of the root canals. When the root canal thirds were compared, OB and RE were more effective in the cervical third than in the apical third (p < 0.05). In conclusion, Resilon and EndoFlow gutta-percha were effective in filling lateral canals by using the Obtura II system.
Keywords: Endodontics; Gutta-percha; Root Canal Obturation; Root Canal Filling Materials